Rheometric study on the gelation process of the compositions of interpenetrating polymer networks made of polyurethane and unsaturated polyester - Król, P.; Wojturska, J. (Polimery, 2022)
Rheometric investigations on the process of gelation of UP/PUR compositions, type IPN, with styrene (ST) have been done. Rheological parameters of series of such systems, differing in compositions, from the moment of crosslinking reaction initiation up to the gelation point (Table 1) were determined. The results obtained allowed to explain the effects of macrokinetics of gelation on the type of microstructure of forming IPN composition and dynamic mechanical properties resulting from it (storage modulus - , loss modulus and loss tangent - tg d) (Fig. 1-8). It was found that the character of changes of rheological factors and mechanical properties depends on PUR and ST contents in the system. The chemical structure of the initial polyurethane network is of less importance. Gelation time of IPN compositions is in the range from 140 s up to even 1300 s. It was demonstrated that high initial amount of styrene and low PUR content in the system led to faster formation of crosslinked structure. In cases of the systems containing > 20 % of PUR or low content of styrene in UP (10 wt. %) the gelation process is going so slowly that the criterion of determination of intersection point of the curves describing and versus time cannot be applied. The shorter gelation times of the compositions the larger the values of Young’s modulus of cured polymers, determined at room temperature (20 °C - Table 2 and 3, Fig. 9). Such behavior results from the formation of the particular type of microstructure of fast gelating systems i.e. two-phase system with unary matrix, formed by crosslinked polyester resin, and binary dispersed phase, composed from the mixture of PUR and crosslinked UP. In slowly gelating systems with high PUR content the two-phase cured structure consists of binary PUR - UP matrix and unary UP dispersed phase.